PENGEMBANGAN MEDIA PETA PUZZEL DALAM PEMBELAJARAN IPS MADRASAH IBTIDAIYAH USWATUN HASANAH MERAMBUNG - Saifullah Saifullah; Pargito Pargito; Darsono Darsono (Faculty of Teacher Training and Education, University of Lampung, 2013)
The objective of this research is to fine a media of instructional such as puzzle map Lampung Province to be applied in social studies learning. Approach the used is Researchand and Development (RD). Result so fresearch and development are: Instructional media named puzzlemap Lampung provincein 2013th, Puzzle shapes are applied is jigsaw puzzle, Consists of a mappuzzle piecesdistricts/cities throughout theprovince ofLampung. Map Lampung provincein 2013 can be presented vertically andhorizontally. Mappuzzle according to Jean Piaget's theory of development, materialin the form of map elements and the conditions that existin the map with the coordinates of point accuracy and proper scale. Mappuzzle to be used primarily in the Basic Competency, “Readmapslocal neighborhood (district/city, province) using asimplescale